Addressing Nigerian Economic Challenges through the Instrumentality of the Law - Amupitan, Joash Ojo (Journal of Sustainable Development Law and Policy, 2025)
“Under the new dispensation, lawyers should be more involved in political and social engineering. Being the light bearer by virtue of their special training, they should bear the light at every dark enclave to show hidden attempts at the lawyer in misgovernance, misrule, and maladministration. The new dispensation must be dogged and determined fighter for freedom and equity and to ensure that the ordinary citizen is protected from threatened abuse of his fundamental rights through reckless and arrogant exercise of state powers the lawyers should take their pride of place in society. They should jettison the garb of eggheads living like strangers in a splendid isolation in his own society oblivious of important development in the economic and social affairs of his country. The lawyers` role in the new policy should be that of an active participant in the platonic search for common good”. Aare Afe Babalola, SAN